An index-based approach to assess the vulnerability of coffee-based farmers to climate change and variability across districts in Western Ethiopia - Akafu, Tesfaye; Korecha, Diriba; Garedew, Weyessa; Amare, Abayineh (Frontiers in Climate, 2025)
Coffee farming supports the livelihoods of over 15 million people in Ethiopia. However, approximately 90% of Ethiopian coffee producers are smallholders, making them among the most vulnerable to global change because of their limited resources and high dependence on family labor. This study examined the vulnerability of coffee-based farmers to climate change and variability across five districts in the West Wolega Zone of Western Ethiopia. The study combined primary and secondary data. A cross-sectional research design was used to collect primary data from 642 household heads, using 35 vulnerability indicators. Secondary data was obtained from the Ethiopian Meteorological Institute (EMI). The Livelihood Vulnerability Index (LVI) and Livelihood Vulnerability Index-Intergovernmental Panel on Climate Change (LVI-IPCC) framework were used for data analysis. The LVI indicated that coffee producers in Gimbi district (0.387) were more vulnerable to climate change and variability, followed by those in Homa (0.379), Ganji (0.377), Nolekaba (0.370), and Haru district (0.365). The LVI-IPCC analysis showed that coffee farming communities in the Haru districts (0.097) were the most vulnerable to climate change, followed by the Nolekaba (0.089), Homa (0.082), Ganji (0.081), and Gimbi districts (0.077). Spatial disparity in vulnerability is explained by the heterogeneity of socioeconomic and biophysical factors. Food, water, and climate variability contributed to the high vulnerability of farming households in all districts. Overall, farmers in all districts face the highest exposure and sensitivity, combined with a limited adaptive capacity. The findings of this study are crucial for stakeholders and policymakers as they provide essential insights for designing and implementing strategies to reduce vulnerability and improve the adaptability of coffee farming households.